Peran Guru dalam Pembentukan Karakter Peserta Didik Sekolah Dasar Setelah Masa Pandemi Covid-19 - Miftahul Jannah; Nida Mauizdati (IBTIDA, 2022)
The Covid (Corona Virus Disease) pandemic, which has been going on since the end of 2019, apparently lasted a long time, even several semesters. This makes students also undergo online learning for a long time. When face-to-face learning begins to be carried out again, of course, teachers have the obligation to play a deep role in instilling character education in students, who may not be touched during online learning. This study was conducted to determine the teacher's role in character building in face-to-face learning after COVID-19. This study uses a qualitative method, namely looking for data through interviews, observation, and documentation. Then the data are organized, synthesize, and produce conclusions. The results showed that the teacher's role in character education for students in post-covid-19 learning, or after a long period of online learning, was by starting to rebuild routines like before the pandemic, such as returning to routine pickets, disciplining study hours, supervising students in doing assignments. In addition, the teacher also becomes more trying to appear as a figure that can be imitated by students. Teachers also try to provide variety in teaching and increase activities that require interaction between students, because it is social life at school that students cannot feel during online learning. Thus, some of the methods used by the teacher in building this character are the exemplary method, the habituation method, the Advice method, the story method, and the reward and punishment method.